Aboveground biomass estimation of trees in the University of the Philippines Los Baños Campus, Philippines - Dida, Jan Joseph V.; Tiburan, Cristino L., Jr. (2020)
The University of the Philippines Los Baños (UPLB) campus is part of the Mount Makiling Forest Reserve (MMFR) buffer zone. It is home to diverse and unique species of plants and fauna. Given the important role of trees in sequestering atmospheric carbon, the estimation of aboveground biomass(AGB) will be useful in assessing green spaces and campus zoning in UPLB. Tree inventory activities were conducted in the campus to collect information such as geographic location and diameter at breast height of trees. Allometric equations developed for moist tropical zones were used to estimate the AGB of trees inside the campus. A total of 2,947 individual trees belonging to around 151 species were recorded, with Swietenia macrophylla as the most frequent species followed by Pterocarpus indicus. Tree species belonging to larger diameter class yielded higher aboveground biomass values compared to other diameter classes. The conduct of future inventory activities in the UPLB campus will aid in the monitoring of AGB yield and carbon stock through time.
Keywords: Forest biomass; Biomass -- Measurement; Forest management; University of the Philippines (Los Baños); Mount Makiling Forest Reserve